UILITY VECTORS TO FUZZY PREFERENCE RELATION DENGAN METODE SIMPLE ADDITIVE WIGHTING (SAW) DALAM SISTEM PENEMPATAN PEGAWAI BARU - Eliasta Ketaren (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
To improve the performance of companies, employees are one of the important elements in this regard, especially in the placement of new employees. The procedure for placing new employees in this case is done by Fuzzy Logic. Input parameters used are IQ Test, Psychological Test and Academic Test. To expressdecision makers' preferences on the most desirable alternatives, it can be done by transforming the format of preferences of Utility Vectors to Fuzzy Preference Relations. Next, choose the SAW method to determine the weight value for each attribute, followed by the ranking process to select the best alternative, in this case is a suitable alternative to determine the work position of employees in accordance with predetermined criteria. With this method, it is expected that the assessment will be more precise and accurate because it is based on the criteria and weight values that have been determined.